AKTIVITAS ANTIBAKTERI EKSTRAK N-HEKSAN, ETIL ASETAT DAN ETANOL BUNGA SOKA MERAH (Ixora coccinea L) TERHADAP BAKTERI Propionibacterium acnes DAN Escherchia coli - Fitriana Fitriana; Tadjuddin Naid; Rachmat Kosman; Nurul Hasanah; Putri Lestari; Fadelita Huath; Adinda S. Gaffar (As-Syifaa Jurnal Farmasi, 2026)
Red Ixora has been empirically used to treat scabies and gastritis. This study aimed to evaluate the antibacterial activity of red Ixora flower extracts against test bacteria. Extraction was performed using sequential maceration with n-hexane, ethyl acetate, and ethanol as solvents. Antibacterial activity was assessed through Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), agar diffusion assay, and TLC-bioautography. Results showed MIC values of 0.5% for all three extracts, while MBC values were 1% for n-hexane and ethyl acetate extracts and 0.5% for ethanol extract. Agar diffusion assays indicated the largest inhibition zones at 6% and 10%, respectively. TLC-bioautography of n-hexane extract with n-hexane:ethyl acetate (4:1) revealed active spots with Rf values of 0.72 and 0.63; 0.45; 0.27. Ethyl acetate and ethanol extracts with chloroform:methanol:water (15:3:1) showed active spots with Rf 0.78 and 0.61; Rf 0.69 for ethyl acetate, and Rf 0.89; 0.74; 0.61; 0.47 and Rf 0.72 for ethanol. Phytochemical analysis indicated potential presence of alkaloids, flavonoids, and terpenoids. These findings demonstrate that red Ixora flower extracts possess significant antibacterial activity against test bacteria, supporting their potential development as natural product-based pharmaceutical preparations.